Heavy-Atom Tunneling Through Crossing Potential Energy Surfaces: Cyclization of a Triplet 2-Formylarylnitrene to a Singlet 2,1-Benzisoxazole - Nunes, C. M. (2020)
Not long ago, the occurrence of quantum mechanical tunneling (QMT) chemistry involving atoms heavier than hydrogen was considered unreasonable. Contributing to the shift of this paradigm, we present here the discovery of a new and distinct heavy-atom QMT reaction. Triplet syn-2-formyl-3-fluorophenylnitrene, generated in argon matrices by UV-irradiation of an azide precursor, was found to spontaneously cyclize to singlet 4-fluoro-2,1-benzisoxazole. Monitoring the transformation by IR spectroscopy, temperature-independent rate constants (k≈1.4×10-3  s-1 ; half-life of ≈8 min) were measured from 10 to 20 K. Computational estimated rate constants are in fair agreement with experimental values, providing evidence for a mechanism involving heavy-atom QMT through crossing triplet to singlet potential energy surfaces. Moreover, the heavy-atom QMT takes place with considerable displacement of the oxygen atom, which establishes a new limit for the heavier atom involved in a QMT reaction in cryogenic matrices.